Lanthanide complexes of DOTA–nitroxide conjugates for redox imaging: spectroelectrochemistry, CEST, relaxivity, and cytotoxicity. Issue 31 (22nd July 2021) - Mouchel Dit Leguerrier, D.; Barré, R.; Ruet, Q.; Imbert, D.; Philouze, C.; Fries, P. H.; Martel-Frachet, V.; Molloy, J. K.; Thomas, F.
Abstract : The lanthanide(iii ) complexes (Gd, Eu, Dy, and Yb) of DOTA tris(amide) and bis(amide) derivatives (L1 and L2 ) featuring one redox active TEMPO arm were prepared. Abstract : The lanthanide(iii ) complexes (Gd, Eu, Dy, and Yb) of DOTA tris(amide) and bis(amide) derivatives (L1 and L2 ) featuring one redox active TEMPO arm were prepared. Ligand L2 harbours an alkyne fragment for further functionalization. The X-ray crystal structure of ligand L2 in complexation with Na + was solved. The complexes showed in their CV one oxidation wave (0.26–0. 34 V vs. Fc + /Fc) due to an oxoammonium/nitroxide redox couple and a broad reduction corresponding to the nitroxide/hydroxylamine system. The Eu complexes demonstrated the presence of one water molecule in their coordination sphere. The nitroxide complexes were characterized by EPR spectroscopy, showing the typical 3-line pattern in the high temperature regime, which is quenched upon the addition of ascorbate (reduction into hydroxylamine). In their nitroxide form, the complexes show essentially no CEST peak. Conversely, the reduced complexes demonstrate a 12% CEST peak at 51 ppm, corresponding to the metal bound water molecule. Fast exchange precluded the CEST activity for the amide protons. All the complexes proved to be essentially non-toxic for M21 cells at concentrations up to 50 μM.